2008
DOI: 10.1590/s1413-70542008000300035
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biogás no tratamento dos efluentes líquidos do processamento de Coffea arabica L. em reator anaeróbico UASB para o potencial aproveitamento na secagem do café

Abstract: RESUMOEstudou-se a produção de biogás proveniente do tratamento das águas residuárias do processamento por via úmida do café (ARC) coco em sistema de tratamento anaeróbio em escala laboratorial. O sistema foi composto de um tanque de acidificação e equalização (TAE), um reator anaeróbio de manta de lodo e fluxo ascendente (UASB), uma lagoa aerada facultativa (LAF) Termos para indexação: Café, águas residuárias, tratamento anaeróbio, metano. ABSTRACTIt was studied the biogas production through the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 1 publication
0
12
0
9
Order By: Relevance
“…In general, in anaerobic reactors, effluents that fit completely in the patterns of Brazilian environmental legislation are not produced. Therefore, it is necessary to use a system of posttreatment to the polishing of these effluents, as was also observed by PRADO & CAMPOS (2008) and SELVAMURUGAN et al (2010b). The use of post-treatment systems with activated sludge its becoming a viable alternative to improve the quality of effluents from anaerobic reactors (CHERNICHARO, 2007).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In general, in anaerobic reactors, effluents that fit completely in the patterns of Brazilian environmental legislation are not produced. Therefore, it is necessary to use a system of posttreatment to the polishing of these effluents, as was also observed by PRADO & CAMPOS (2008) and SELVAMURUGAN et al (2010b). The use of post-treatment systems with activated sludge its becoming a viable alternative to improve the quality of effluents from anaerobic reactors (CHERNICHARO, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…The results of these studies confirmed that the concentrations of phenols contained in wastewater from wet-processed coffee were not toxic to anaerobic microbiota and can be reduced in UASB reactors in two stages under the conditions studied. However, with higher VOL, such as those applied by PRADO & CAMPOS (2008), the removal of phenols may decrease. With the inclusion of post-treatment with aerobic stage this problem could be mitigated.…”
Section: Efficiency (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…Provavelmente, devido às menores cargas de SST aplicadas, quando comparadas às de ST. Além disso, a maior parte dos SSTs apresentou-se na forma orgânica (SSV) (Tabela 1), o que pode ter facilitado o processo de degradação. Verificou-se que as cargas orgânicas aplicadas neste trabalho estão em conformidade com aquelas encontradas na literatura para o tratamento de águas residuárias provenientes da cadeia produtiva do café, em reatores anaeróbios (BRUNO & OLIVEIRA, 2008;PRADO & CAMPOS, 2008;LUIZ, 2007;DINSDALE et al, 1996). Entretanto, em relação às cargas aplicadas aos SACs, estas foram bem superiores às cargas recomendadas para o tratamento de efluentes domésticos que, segundo USEPA (2000), deve variar de 60 a 133 kg ha -1 d -1 de DBO, mas em conformidade com os autores que avaliaram o tratamento de águas residuárias que apresentam compostos recalcitrantes como a ARC (MASBOUGH et al, 2005;TAO et al, 2006;CALHEIROS et al, 2007;SOHSALAM & SIRIANUNTAPIBOON, 2008 …”
Section: Avaliação Global Do Sistema De Tratamentounclassified